Extending Situated Language Comprehension (Accounts) with Speaker and Comprehender Characteristics: Toward Socially Situated Interpretation - Münster, Katja; Knoeferle, Pia (Frontiers in Psychology, 2018)
More and more findings suggest a tight temporal coupling between (non-linguistic) socially-interpreted context and language processing. Still, real-time language processing accounts remain largely elusive with respect to the influence of biological (e.g., sex or age) and experiential (i.e., world and moral knowledge) comprehender characteristics and the influence of the ‘socially-interpreted’ context, as for instance provided by the speaker. This context could include actions, facial expressions, a speaker’s voice or gaze, and gestures among others. We review findings from social psychology, sociolinguistics and psycholinguistics to highlight the relevance of (the interplay between) the socially-interpreted context and comprehender characteristics for language processing. The review informs the extension of an extant real-time processing account (already featuring a coordinated interplay between language comprehension and the non-linguistic visual context) with a variable (‘ProCom’) that captures characteristics of the language user and with the comprehender’s speaker representation. Extending the CIA to the sCIA (social Coordinated Interplay Account) is the first step towards a real-time language comprehension account which might eventually accommodate the socially situated communicative interplay between comprehenders and speakers or actors.